2019
DOI: 10.1108/jsbed-12-2018-0379
|View full text |Cite
|
Sign up to set email alerts
|

Examining the mediating role of innovativeness in the link between core competencies and SME performance

Abstract: Purpose The purpose of this paper is to evaluate the effect of core competencies, namely, transformational leadership (TFL), entrepreneurial competence and technical competence on financial performance through the mediation effect of innovativeness, among owner-managed small and medium-sized enterprises (SMEs) in developing countries. Design/methodology/approach A research model was developed to test nine research hypotheses. Self-report questionnaires designed for this study were sent to SME owner-managers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 84 publications
0
45
1
3
Order By: Relevance
“…For example, Swoboda and Olejnik (2013) noted two distinct sets of antecedents of SMEs’ performance such as structural and strategy. Moreover, some valuable contributions have been made by the studies of Ng et al (2020), Singh et al (2020), de Zubielqui et al (2019) and Rhee et al (2010) which presented models that focused their attention only on innovation antecedents. Accordingly, Valdez-Juárez et al (2019) and Wang et al (2018) focus on knowledge – learning and human resource antecedents.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Swoboda and Olejnik (2013) noted two distinct sets of antecedents of SMEs’ performance such as structural and strategy. Moreover, some valuable contributions have been made by the studies of Ng et al (2020), Singh et al (2020), de Zubielqui et al (2019) and Rhee et al (2010) which presented models that focused their attention only on innovation antecedents. Accordingly, Valdez-Juárez et al (2019) and Wang et al (2018) focus on knowledge – learning and human resource antecedents.…”
Section: Discussionmentioning
confidence: 99%
“…With the globalization of economies, the sphere of a firm's competitors is no longer limited to the local level and competition between firms is increasingly tough (Hitt et al , 2011). Faced with such a threat to companies, it is crucial that they develop strategies to be competitive and ensure their sustainability (Ng et al , 2019). With this in mind, there is an abundant literature in strategic management on approaches that a company can take to control competition (Hutzschenreuter and Gröne, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Start-ups as a new form of SMEs that boost entrepreneurial potential usually represent an interdisciplinary team composition, hence researchers have spotted the positive influences of multiple cross-disciplinarity toward the development of entrepreneurial capital [49], which is a function of entrepreneurial competences and entrepreneurial commitment [50]. More recent studies reported the crucial role of transformational leadership, entrepreneurial competence, technical competence and innovativeness as core to owner-managed SMEs [51]. It is worth mentioning that researchers found coaching to be an instrument for entrepreneurs' support in leadership development and new idea implementation [52].…”
Section: Introductionmentioning
confidence: 99%